2015
DOI: 10.4236/aer.2015.32005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase Hydrolysis of Organic Phosphorus Compounds

Abstract: Phosphatases are diverse groups of enzymes that deserve special attention because of their significant roles in organic phosphorus (OP) mineralization to inorganic available forms (Pi). This work 1) compared the catalytic potentials of commercially acid phosphatase from wheat germ, sweet potato, and potato, and alkaline phosphatase from E. coli; 2) demonstrated that the rate of hydrolysis, catalytic efficiency, thermal stability, and optimal pH of these enzymes depended on enzyme sources and the stereochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This may owing to the ability of mycorrhiza to increase root surface area to uptake mineral contents and make phosphorus absorpable by plant roots. This result was in agreement with the finding of Pagano et al (2010) who reported that VAM colonization was significantly higher with the inoculated seedlings versus non-inoculated ones (control) and Tazisong et al (2015) who said that Phosphatases are responsible for the hydrolysis of a range of organic P compounds and provide mineral phosphate to the plant. Furthermore, Matias et al (2009) reported that the intensity of VAM colonization was also stimulated by plant growth.…”
Section: Discussionsupporting
confidence: 92%
“…This may owing to the ability of mycorrhiza to increase root surface area to uptake mineral contents and make phosphorus absorpable by plant roots. This result was in agreement with the finding of Pagano et al (2010) who reported that VAM colonization was significantly higher with the inoculated seedlings versus non-inoculated ones (control) and Tazisong et al (2015) who said that Phosphatases are responsible for the hydrolysis of a range of organic P compounds and provide mineral phosphate to the plant. Furthermore, Matias et al (2009) reported that the intensity of VAM colonization was also stimulated by plant growth.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphatases are responsible for the hydrolysis of a range of organic P compounds and provide mineral phosphate to the plant (Tazisong et al, 2015 ). In our study, increased acid and ALP was observed in A. gerrardii grown under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…b Bacterial phylogenetic tree depicting the evolutionary relationships between 16 phyla present in the study system. At 2500 Myr, coloured circles indicate eight extant phyla and the most recent common ancestors of the clades Chloroflexi-OD1-TM7 and Planctomycetes-Verrucomicrobia-Gemmatimonadetes -Acidobacteria-Nitrospira same family (e.g., phosphatases) depending on their biological origin [75]. The more effective niche filling with differentiated recent lineages would ultimately explain the correlation between high PD and EFs [25].…”
Section: Discussionmentioning
confidence: 99%